KONFLIK KELUARGA PADA ANAK YANG BERCITA-CITA MENJADI ATLET ESPORTS - Muhamad Affan Akmaldy (2023)
The conflict between parents and adolescents arises as a result of disagreements and differences of opinion. For gamers, the presence of the esports industry serves as a platform for those who wish to generate something from playing games. However, there are numerous negative stigmas associated with the world of gaming and esports from the perspective of parents. This research focuses on examining the factors that influence family conflict in children aspiring to become esports athletes. The study employs a qualitative approach with a phenomenological method. Data collection is conducted through snowball sampling with four informants and also involves their parents. The research findings indicate that several factors can contribute to family conflict in children aspiring to become esports athletes. However, despite being engaged in conflict, it does not have a negative impact on the parent-child relationship. In conclusion, three factors influence family conflict in children aspiring to become esports athletes: family type, differences in parental and child views on esports, and generational gaps. The suggestion offered by the researcher is the need for open communication between children and parents to find common ground or agreement.